Impacts and Implications of Korea-EU FTA to Agricultural Sector after 5 Years of Effectuation - 한석호 (한국농촌경제연구원, 2016)
○ In the 5th year of implementation of the Korea-EU FTA, the volume of trade of agricultural and livestock products between two parties was reduced compared to the 4th year due to the impact of change in domestic and overseas conditions; however, it increased compared to a normal year before the pact went into effect. - In the 5th year of implementation, the value of import of agricultural and livestock products from the EU stood at USD 3.5 billion, down by 4.7% than the previous year and up by 68.2% than an average year before the effectuation. - In the 5th year of implementation, the value of export of agricultural and livestock products to the EU was USD 340 million, down by 1.5% than the previous year and up by 68.2% than a normal year before the effectuation. ○ In 2015, the utilization rate of preferential tariffs for agricultural and livestock products imported from the EU was 82.2%, while the rate for products exported to the EU was 69.5%. - Items whose rate of utilizing FTA preferential tariffs for import is 90% or over among products with USD 100 million of the value of import or over include pork, cheese, wine, etc. - Items whose rate of utilizing FTA preferential tariffs for export is 90% or over among products with USD 10 million of the value of export or over include gelatin, ramen, etc. ○ Due to reduction of tariffs for the Korea-EU FTA and decreased domestic production, the volume of pork imported from the EU increased by 2.1% compared to the 4th year and 76.0% compared to an average year before the effectuation. - Although competition became intensified, including conclusion of FTAs with dairy product exporting countries such as Australia and New Zealand, the volume of import of dairy products in the 5th year of implementation rose by 14.9% compared to the previous year and 146.0% than a normal year before the effectuation due to an increase in the production of dairy products in the EU and decline in prices. - The volume of import of corn and barley increased compared to the 4th year of implementation; with a decrease in the imports of wheat, however, the total volume of import of grain from the EU dropped by 2.7% compared to the previous year and grew by 369.9% compared to an average year before the effectuation. ○ Thanks to reduction of tariffs, the effect of decreasing import price was achieved in the 5th year of implementation, including the import price of pork down by 8-17%, dairy products by 8-16% and grain by 3-28%. ○ As part of domestic measures to deal with the impact of opening the market by the Korea-EU FTA, performance in policy was ensured, including improvement of stockbreeding productivity and spread of eco-friendly stockbreeding. - From 2011 to 2015, the budget of KRW 4 trillion and 838.4 billion was executed for domestic measures to supplement the Korea-EU FTA (86.8% compared to the initial plan). - Projects for modernizing livestock facilities contributed to improving the productivity of each livestock type, and projects for vitalizing natural recycling agriculture and supporting livestock manure processing facilities served spreading eco-friendly livestock production.